The Self-Perception Theory vs. a Dynamic Learning Model - Otto H. Swank (Tinbergen Institute, 2006)
Several economists have directed our attention to a finding in the social psychological literature that extrinsic motivation may undermine intrinsic motivation. The self-perception (SP) theory developed by Bem (1972) explains this finding. The crux of this theory is that people remember their past decisions and the extrinsic rewards they received, but they do not recall their intrinsic motives. In this paper I show that the SP theory can be modeled as a variant of a conventional dynamic learning (DL) model. A comparison between the assumptions underlying the SP model and the DL model shows that the SP model could be relevant in a wide variety of educational contexts. However, the SP model seems ls relevant than the DL model in other contexts.
Keywords: D82; D83; 330; Self-Perception Theory; Dynamic Learning; Incentives; Intrinsic Motivation